Lucjan Rydel i teatr - Kowalska , Agnieszka (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
In my article I make an assumption that theatre was a crucial part of Lucjan Rydel artistic work. He worked in the theatre and for the theatre as a playwright, theatre critic, director, literary director, lecturer in theatre school, member of theatre committee, theatre producer and director of a city theatre. It is almost impossible to describe the whole range of Rydel’s professions. However, a deep analysis would reveal his different faces of this talented man. In this article I focus on the work of Rydel as a theatre practitioner, mainly on staging his own dramatic works. I claim that he had a deep knowledge of actors’ craft and skills, of staging methods and styles. I hope that thesis included in the article will encourage theatre historians to further research